Kinetic Evidence of Tautomerism of Thiourea Dioxide in Aqueous Acidic Solutions. Issue 11 (13th March 2014) - Csekő, György; Hu, Ying; Song, Yanan; Kégl, Tímea R.; Gao, Qingyu; Makarov, Sergei V.; Horváth, Attila K.
Abstract: Indirect experimental evidence of the existence of a sluggish tautomerism of thiourea dioxide in acidic aqueous solution was discovered while studying its oxidation by chlorine dioxide. Thiourea dioxide slowly rearranges into aminoiminomethanesulfinic acid, but the reactivity of these two species towards chlorine dioxide marginally differs. It was clearly demonstrated that thiourea dioxide reacts with chlorine dioxide in a relatively slow reaction in an autocatalytic fashion with respect to the carbon(IV) species. In contrast, reaction of aminoiminomethanesulfinic acid with chlorine dioxide is orders of magnitude faster but proceeds through a normal second‐order process. Abstract : Kinetic evidence of the tautomerism of thiourea dioxide in aqueous acidic solutions is reported. The reactivity of the two tautomeric forms towards ClO2 significantly differs in rate and also in mechanistic aspects. Whereas aminoiminomethanesulfinic acid reacts with ClO2 in a second‐order process, the reaction of its tautomeric form, thiourea dioxide, with ClO2 displays autocatalysis.